Profiling Serum and Tissue Biomarkers of Vedolizumab Therapy Response in Inflammatory Bowel Disease. - O'Connell, James William (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Introduction: Vedolizumab (VDZ) is a novel biologic agent proven effective for Inflammatory bowel disease (IBD), however, a significant proportion of patients do not respond to VZD treatment Aims: This thesis evaluates potential predictive markers, trough drug levels and inflammatory markers, of VDZ treatment outcome in patients with IBD to enable early identification of responders and non-responders. Using the UC explant model, the impact of VZD on the colonic secretome and the cross talk between the colonic explant secretome and peripheral blood mononuclear cells is examined. Methods: This is a multicentre prospective study of IBD patients receiving VDZ therapy. Patients aged ¿18 years with IBD, due to start, or receiving VDZ were recruited from three medical centres in Ireland. Ethical approval was received from St James and Tallaght University Hospitals, St Vincent¿s University Hospital, and Connolly and Beaumont Hospitals. Written informed consent was obtained prior to enrollment. Baseline demographics and clinical data were obtained by patient questionnaire complemented by medical record review. IDKmonitor® VDZ drug level/Anti-VDZ ELISA, was used for VDZ drug and antibody assays. A V-PLEX Human Biomarker 54-plex ELISA kit (including vascular injury, cytokine, TH17, angiogenesis, proinflammatory, and 2 chemokine panels) was used to assay serum and colonic explant conditioned media. Tissue explants were generated from endoscopic colonic biopsies and PBMCs isolated from a single healthy donor blood pack. Statistical analyses was performed using SPSS (version 26.1.2;) and graphs constructed with GraphPad Prism (version 5.01). Results: In 34 patients established on VDZ therapy, maintenance trough levels did not associate with disease activity nor was there a correlation with known biomarkers of disease activity (serum CRP, albumin, faecal calprotectin). Forty patients commenced VDZ, with median 17.8 [range 0.5¿41] months follow-up. At week 14, 18/40 (45%) and at week 30, 15/40 patients (40%) were in steroid free remission(SFR). Higher week 6 VDZ trough concentrations associated with weeks 14 (p=0.015) and 30 (p=0.029) SFR. A week 6 trough VDZ of ¿15.5µg/mL predicted week 14 SFR (sensitivity 82.5%, specificity 65%, p=0.017) and week 30 SFR; (sensitivity 86.7%, specificity 63.6%, p=0.006). Those with week 6 trough concentration of ¿15.5µg/mL were more likely to persist on VDZ compared with those with a trough <15.5µg/mL (p=0.004). VDZ trough concentrations were significantly higher, median 22.5 [15.5-28.9] µg/mL with baseline CRP <5mg/L compared to CRP ¿5mg/L, 9.9 [6.5-20.4]µg/mL, p=0.01. Of 39 patients with serum measurements of 54 inflammatory markers at baseline at week 6 of therapy, in univariate analysis, higher baseline concentration of TNF-ß (p=0.0003) and lower concentration of IL-22, VEGF-C and IL-7 (p=0.034, p=0.042, p=0.045, respectively) associated with week 14 SFR. Higher baseline concentrations of IL-4, MDC, and MCP-4 (p=0.011, p=0.026, p=0.028 respectively) and lower concentrations of IL-10 (p=0.03) associated with week 30 SFR. None retained significance following multiple test correction. Following 6 weeks VDZ induction, concentrations of serum eotaxin, and eotaxin 3 were significantly increased (p=0.0012, p=0.0013 respectively) and IL-15 decreased (p=0.0004) at week 6 compared to baseline when corrected for multiplicity. Prior anti-TNF therapy had no effect on the 35 inflammatory proteins analysed in the UC explant secretome. Onset of VDZ action was rapid with alterations in the secretome detected following 24 hours VDZ incubation. Concentrations of IP-10, MDC, and IL-21 were lower (p=0.016, p=0.039, p=0.05 respectively) in the VDZ treated samples compared to controls. IL-15 concentrations were lower in supernatant of PBMCs stimulated with VDZ treated explant culture medium compared to controls consistent with the earlier findings of decreased serum IL-15 concentrations following VDZ induction. Conclusions: Week 6 trough levels are clinically useful and can predict risk of treatment failure. Maintenance trough levels were not useful. Baseline CRP is also useful in identifying those at risk of disease failure, conversely a baseline CRP <5mg/L associates with higher VDZ trough levels and could be used as a surrogate marker of adequate VDZ dosing. The feasibility of using the explant model to interrogate the colonic secretome is shown with the rapid onset of VDZ action within the local tissue microenvironment that may be independent of the ¿4ß7 integrin pathway. Findings in this thesis add to the existing knowledge base regarding VDZ use in IBD.
APPROVED
Keywords: Gastroenterology; Inflammatory Bowel Disease; Serum Profiling; Ulcerative Colitis; Crohn's Disease